(untitled) (Revista Contexto & Educação, 2023)
Requirements Engineering is an important activity in the software development process responsible for extracting and defining the needs of the system. This article aims to learn about the main concepts of constructivist theory in order to apply a teaching activity on the theme of Requirements Engineering for a Technology course. It presents the conduct of the experience of an activity to introduce the content on Requirements Engineering, in the course of Analysis and Design of Systems, in the fourth level of the Technology System in Analysis and Development of the Federal Institute of Education, Science and Technology of Rio Grande do Sul – Campus Sertão. The proposed educational practice is based on constructivism that alludes to a theory, a way of being of knowledge or a movement of thought that reveals itself in the advance of the sciences and philosophy of the last centuries. This practice aimed at the student’s active participation in the teaching-learning process based on an analogy with recreational, board and card games. The results suggest that the students were able to relate the learning of the game with the content of the class and achieved the expected knowledge.